IMAGING DIAGNOSIS—TEMPOROMANDIBULAR JOINT DYSPLASIA IN A BASSET HOUND. Issue 5 (1st August 2013) - Lerer, Assaf; Chalmers, Heather J.; Moens, Noel MM; Mackenzie, Shawn D.; Kry, Kristin
<x xml:space="preserve">Abstract</x> A 5‐month‐old intact male Basset Hound presented for evaluation of pain and crepitation during manipulation of the temporomandibular joint, worse on the right side. A computed tomography (CT) scan of the head was performed. The CT images demonstrated the osseous features of temporomandibular joint dysplasia and facilitated a 3D reconstruction, which allowed better visualization of the dysplastic features. The patient responded to conservative management with a tape muzzle with no recurrence reported by the owner 6 months after presentation.